Legal Counseling About the Problems of the Misuse of Pawned Goods - Isdiyana Kusuma Ayu (Jurnal Dedikasi Hukum, 2023)
Guaranteeing goods in pawn guarantees often creates legal problems. One of the problems that arise is that creditors misuse pawn goods. Legal counseling on pawning to the community will first be carried out by exploring and identifying problems with pawn law that occur in the community. After the counseling, an evaluation will be given through question-and-answer interaction so that the level of success of the legal counseling that has been given can be known. In addition, the evaluation was carried out by distributing questionnaires to participants. Based on some of these evaluations, the results show that there has been an increase in public understanding regarding pawn law, the problems of abuse of pawn goods, and legal settlements when pawn law problems occur.   Abstrak Penyuluhan Hukum Tentang Problematika Penyalahgunaan Barang Gadai. Penjaminan barang dalam penjaminan gadai seringkali menimbulkan permasalahan hukum. Salah satu permasalahan yang timbul yaitu kreditur melakukan penyalahgunaan barang gadai. Penyuluhan hukum tentang gadai terhadap masyarakat ini terlebih dahulu akan dilakukan penggalian dan pengidentifikasian permasalahn hukum gadai yang terjadi di masyarakat. Setelah penyuluhan akan diberikan evaluasi melalui interaksi tanya-jawab sehingga dapat diketahui tingkat keberhasilan penyuluhan hukum yang telah diberikan. Selain itu, evaluasi dilakukan dengan cara penyebaran kuisioner kepada peserta. Berdasarkan beberapa evaluasi tersebut maka didapatkan hasil bahwa terjadi peningkatan pemahaman masyarakat terkait hukum gadai, problematika penyalahgunaan barang gadai, dan penyelesaian hukum Ketika terjadi permasalahan hukum gadai.